A mathematical model of a theoretical sleeping sickness vaccine. Issue 2 (2nd April 2016) - Samia, Yasmine; Kealey, Alison; Smith?, Robert J.
ABSTRACT: Human African sleeping sickness is found throughout sub-Saharan Africa. It affects up to 70, 000 individuals per year, primarily the poor. Existing treatments are limited, costly, and often toxic. Recent evidence suggests that a vaccine may be viable. Potential vaccines against Rhodesian sleeping sickness may be imperfect, may only be delivered to some proportion of the population, may wane over time, and may not always mount an immunogenic response in the individual receiving it. The potential effects of such a vaccine are addressed and compared to vector control. The basic reproductive ratio for both unvaccinated and vaccinated individuals is derived. The fitness ratio is used to show that vaccines that grant longer life must be accompanied by a corresponding reduction in transmissibility. A sensitivity analysis shows that control of tsetse flies through insecticide is superior to an idealized vaccine. Such a vaccine is unlikely to eradicate the disease, even if delivered to 100% of the population. Consequently, efforts to control sleeping sickness that do not incorporate vector control may be flawed.